Effectiveness of combination of ginger and B6 with acupressure point PC6 and ST36 in reduce emesis - Anita Iriani; Resi Galaupa (Science Midwifery, 2023)
Based on a preliminary study at Anita Iriani's PMB, which was conducted in June 2022, out of 43 first trimester pregnant women, a percentage of 32 people with nausea and vomiting and 11 pregnant women without nausea and vomiting were obtained. In the first trimester, the incidence of nausea and vomiting in pregnant women is higher than in pregnant women without nausea and vomiting. This type of research is Quasy Experimental with pre-test and post-test with control group design. This study will compare the 2 groups given the pre-test and post-test with the aim of knowing the condition of the group before and after being given the intervention on the effect of the combination of ginger and B6 (Pyrindoxine) with PC6 and ST36 acupressure points in reducing emesis in first trimester pregnant women in PMB Anita Iriani, Bekasi Regency.